Ketergantungan Ekonomi dan Kekerasan dalam Rumah Tangga: Mengungkap Hambatan di balik Kasus yang Tidak Terungkap (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2025)
Domestic violence is a social problem that is still significantly ongoing in various levels of society, despite many efforts to provide protection to victims. One of the factors that often hinders victims from reporting violence is economic dependence on the perpetrator. This dependence creates complex situations, where victims feel trapped between the need to survive and fear worse consequences if they resist or report the violence they experienced. Economic dependence often worsens the psychological condition of the victim, affects their decision-making, and causes them to feel they have no choice but to remain in a violent relationship. This article aims to dig deeper into economic dependence factors as the main cause of why many cases of domestic violence are not revealed. In addition, this article will also explore
Keywords: Domestic Violence; Women; Dependence; Economy